Price Experimentation and Security Market Structure - Leach, J. Chris; Madhavan, Ananth N. (Review of Financial Studies, 1993)
[We examine the role of market makers in facilitating price discovery. We show that a specialist may experiment with prices to induce more informative order flow, thereby expediting price discovery. Market makers in a multiple-dealer system, unlike a specialist system, do not have the incentives to perform such costly experiments because of free-rider problems. Consequently, the specialist system may provide open markets where competition fails but at the cost of wider bid-ask spreads. We analyze the effect of experimentation on the bid-ask spread and provide an exploratory analysis of intraday specialist data that is consistent with our price experimentation hypothesis.]